Extra Buoyancy and Mesh Size as The Measuring Indicators for the Effectiveness and Selectivity of Purse Seine in Sampang Waters of Madura - Fuad Fuad; Guntur Guntur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
Fishing gear effectiveness is a main parameter to measure effiency rate of fishing operation. At same time, fishing gear selectivity becomes a main consideration in preserving fish resources. Nowadays, the sustainability of fish resources is threatened because all fishers are attempting to narrow their net mesh size to increase their haul. The scarcity of fish resources and the increase of operational cost are dilemmas that can obstruct the implementation of effective and selective fishing operation based on the principle of fish resources conservation. The objective of research is to understand the effectiveness and selectivity rates of fishing gear. The indicators used to measure the effectiveness of fishing gear are boat speed during fishing activity and fish haul rate. Fishing gear selectivity is measured by comparing fish length during gonad mature and fish length during firstly-caught. This fishing gear selectivity is also used as the indicator of environmentally friendliness rate of purse seine. The calculation of fishing gear selectivity is begun by determining fish size at caught (Lc) and fish size at gonad mature (Lm) and then comparing both sizes with mesh size of purse seine.Result of research indicates that effective speed of fishing operation is achieved when boat speed is 7.1 knots with fish haul rate of 1,000 kg and with fishing operation time of 2,853 seconds. Fishing operation speed above 8 knots is not efficient because it produces quite significant increase of fuel consumption although fish haul rate remains similar. Purse seine used in Sampang waters is not selective because the size of mackerel fish (selaroides spp) at firstly-caught (Lc) is smaller than fish length at gonad mature (Lm), thus Lc < Lm. Fish size at gonad mature (Lm) is 19.35 cm, while fish size at firstly-caught is 18.6 cm. Regression analysis indicates that there is a close relationship between fish length and fish weight, which is scored at 84 %